Bioabsorbable Implant for Treatment of Nasal Valve Collapse with or without Concomitant Procedures - Sidle, Douglas M.; Stolovitzky, Pablo; O'Malley, Ellen M.; Ow, Randall A.; Nachlas, Nathan E.; Silvers, Stacey (Facial Plastic Surgery, 2021)
The aim of the study is to report outcomes after treatment of nasal valve collapse with a bioabsorbable nasal implant. It involves two prospective, multicenter, post-market studies evaluating long-term effectiveness of the LATERA implant for severe to extreme nasal obstruction. Participants underwent implant alone or with concomitant inferior turbinate reduction (ITR) and/or septoplasty. Outcome measures included the change from baseline Nasal Obstruction Symptom Evaluation (NOSE) scores, NOSE responder rates, visual analog scale (VAS) scores, and adverse events. A total cohort of 277 participants (109 implants only, 67 implants + ITR, 101 implants + septoplasty + ITR) enrolled at 19 U.S. centers was available for analysis with 177 participants (69 implants only, 39 implants + ITR, 69 implants + septoplasty + ITR) available at 2 years. The mean changes from baseline in NOSE scores and VAS scores were statistically significant (p < 0.001) at all follow-up periods. The baseline NOSE score of 77.8 ± 13.6 was improved to 24.2 ± 23.6 at 24 months. Greater than 90% of participants were NOSE responders across all follow-up periods, 6.1% withdrew for lack of treatment effect. The baseline VAS score of 66.7 ± 18.8 was improved to 21.1 ± 23.9 at 24 months. There were no serious adverse events related to the device or implant procedure. Implant retrieval rate was 4.0% (22/543 implants). Nonserious adverse events were mild to moderate in severity, typically occurred within 6 months of implant, and resolved or were stable. Significant reductions in NOSE and VAS scores and high responder rates from our large population of patients with nasal obstruction who had nasal valve implants confirm sustained effectiveness at 24 months after treatment. The studies are registered on www.clinicaltrials.gov (NCT02952313 and NCT02964312).
Keywords: nasal valve collapse; nasal airway obstruction; bioabsorbable implant; lateral wall insufficiency; nasal valve repair